Consciousness, brain, neuroplasticity - Askenasy, Jean-Jacques M.; Lehmann, Joseph (Frontiers in Psychology, 2013)
Subjectivity, intentionality, self-awareness and will are major components of consciousness in human beings. Changes in consciousness and its content following different brain processes and malfunction have long been studied. Cognitive sciences assume that brain activities have an infrastructure, but there is also evidence that consciousness itself may change this infrastructure. The two-way influence between brain and consciousness has been at the center of philosophy and less so, of science. This so-called bottom-up and top-down interrelationship is controversial and is the subject of our article. We would like to ask: how does it happen that consciousness may provoke structural changes in the brain? The living brain means continuous changes at the synaptic level with every new experience, with every new process of learning, memorizing or mastering new and existing skills. Synapses are generated and dissolved, while others are preserved, in an ever-changing process of so-called neuroplasticity. Ongoing processes of synaptic reinforcements and decay occur during wakefulness when consciousness is present, but also during sleep when it is mostly absent. We suggest that consciousness influences brain neuroplasticity both during wakefulness as well as sleep in a top-down way. This means that consciousness really activates synaptic flow and changes brain structures and functional organization. The dynamic impact of consciousness on brain never stops despite the relative stationary structure of the brain. Such a process can be a target for medical intervention e.g. by cognitive training.